DINÂMICA (2002-2011) E MODELAGEM DO INCREMENTO DIAMÉTRICO EM FRAGMENTO DE FLORESTA OMBRÓFILA MISTA NA FLORESTA NACIONAL DE IRATI, PARANÁ - Roik, Mailson (2012)
The purpose of this work was to analyze the floristic composition, horizontal structure, forest dynamics, and to test the hypothesis that the data stratification performed by the cluster analysis could improve the diameter increment modeling of species from the Araucaria Forest. Effects of adding other dimensional variables besides diameter at breast height (DBH) was also evaluated, as sociological position, site and competition. Data from 25 permanent sample plots of 1 ha in size each were used. All the individuals with diameter at breast height equal or larger than 10 cm (DBH ?10 cm) were identified and measured in the years 2002, 2005, 2008 and 2011. Changes on the floristic composition were analyzed by the presence or not of the individuals in every period evaluated. The horizontal structure was characterized according to the phytosociological parameters of density, frequency and dominance of species, as well as the importance value. The dynamics process of the forest evaluated were the increment, recruitment and mortality. The increment modeling was performed for the whole forest, ecological groups and species groups defined by the cluster analysis according to the mean diametric increment for the species and diameter classes. The diameter increment modeling was performed in two ways: in the first one, eight mathematical models were applied, presenting as independent variable only the DBH; and in the second one, equations were generated by the Stepwise method, presenting as variables other dimensional variables, sociological position, site and competition. The forest presented few changes concerning its floristic composition and species diversity. Along the nine years of monitoring, 124 tree species were registered, including 84 genera and 42 botanical families. The number of individuals decreased in the evaluation period, whereas the number of genera and species increased. Myrtaceae family presented the greatest importance, with the highest number of species and recruited individuals (22.3% of the total). The forest presented an average increment of 0.23cm/year, and 0.21 m?/ha/year in basal area, with highlight to Araucaria angustifolia, which presented the most expressive increments (0.42 cm/year in diameter and 0.12 m?/ha/year in basal area). The average mortality rate of the forest was greatest than the recruitment rate (1.69% and 1.31%, respectively). The utilization of other independent variables, besides DAP, for the estimation of the diameter increment, has improved the fitting, reducing the standard error of estimate and increasing the determination coefficient. The variables most correlated with diameter increment were the shape and position of the crown. Data clustering according to the similarity on the species increment did not make the models suitable to estimate the diameter increment, although, it has improved the models, reducing the standard error of estimate.